Steroidogenic differentiation of human amniotic membrane-derived mesenchymal stem cells into a progesterone-/androgen-producing cell lineage by SF-1 and an estrogen-producing cell lineage by WT1−KTS - Miyazaki, Yumiko; Orisaka, Makoto; Fujita, Yuko; Mizutani, Tetsuya; Yazawa, Takashi; Yoshida, Yoshio (Frontiers in Endocrinology, 2024)
Background: Sex steroid hormones, primarily synthesized by gonadal somatic cells, are pivotal for sexual development and reproduction. Mice studies have shown that two transcription factors, steroidogenic factor 1 (SF-1) and Wilms' tumor 1 (WT1), are involved in gonadal development. However, their role in human gonadal somatic differentiation remains unclear. We therefore aimed to investigate the roles of SF-1 and WT1 in human gonadal steroidogenic cell differentiation.Methods: Using a transient lentivirus-mediated gene expression system, we assessed the effects of SF-1 and WT1 expression on the steroidogenic potential of human amniotic membrane-derived mesenchymal stem cells (hAmMSCs).Results: SF-1 and WT1-KTS, a splice variant of WT1, played distinct roles in human steroidogenic differentiation of hAmMSCs. SF-1 induced hAmMSC differentiation into progesterone-and androgen-producing cell lineages, whereas WT1-KTS promoted hAmMSC differentiation into estrogen-producing cell lineages.Our findings revealed that SF-1 and WT1-KTS play important roles in human gonadal steroidogenic cell differentiation, especially during ovarian development. These findings may pave the way for future studies on human ovarian differentiation and development.